2019
DOI: 10.1080/19476337.2019.1603172
|View full text |Cite
|
Sign up to set email alerts
|

The effect of selected methods of heat treatment on the chemical composition, colour and texture parameters of longissimus dorsi muscle of wild boars

Abstract: The aim of this study was to analyse the impact of differentiation of cooking and baking temperatures on the chemical composition, colour, sensory evaluation, shear force and muscle texture parameters of the longissimus dorsal muscle of wild boars. It was shown that the increase in the final temperature during cooking and baking caused a decrease in the water content in the muscle, and as a result of the density of the tissue structure after the loss of this component, the fat content in the meat after heat tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
2
6
1
Order By: Relevance
“…Carcass weight varied significantly across the animals' age groups, whereas no significant differences were found between sexes within groups (Table 1). Similar carcass weights were reported for wild boars of a similar age (that were harvested in Poland) by Sales and Kotrba (2013) and Dzierżyńska-Cybulko and Fruziński (1997) in their review articles. On the other hand, the weights observed in the present study differ from those reported by Korzeniowski et al (1991b): piglet carcasses were heavier (25 kg vs. 19 kg in Korzeniowski et al, 1991b, and this study respectively), whereas the carcasses of yearlings (37 kg vs. 40 kg in Korzeniowski et al, 1991b, and this study respectively) and older animals (55 kg vs. 62 kg in Korzeniowski et al, 1991b, and this study respectively) were lighter.…”
Section: Carcass and Primal Cuts' Weightssupporting
confidence: 78%
See 3 more Smart Citations
“…Carcass weight varied significantly across the animals' age groups, whereas no significant differences were found between sexes within groups (Table 1). Similar carcass weights were reported for wild boars of a similar age (that were harvested in Poland) by Sales and Kotrba (2013) and Dzierżyńska-Cybulko and Fruziński (1997) in their review articles. On the other hand, the weights observed in the present study differ from those reported by Korzeniowski et al (1991b): piglet carcasses were heavier (25 kg vs. 19 kg in Korzeniowski et al, 1991b, and this study respectively), whereas the carcasses of yearlings (37 kg vs. 40 kg in Korzeniowski et al, 1991b, and this study respectively) and older animals (55 kg vs. 62 kg in Korzeniowski et al, 1991b, and this study respectively) were lighter.…”
Section: Carcass and Primal Cuts' Weightssupporting
confidence: 78%
“…The collagen content reported by other authors varies widely. In some studies, the collagen content of the LTL muscle was lower than in our study, 0.5 % (Oshima et al, 2009) and 0.4 % (Rede et al, 1986), whereas other authors reported a considerably higher collagen content, up to 1.8 % (Korzeniowski et al, 1991a;Dzierżyńska-Cybulko and Fruziński, 1997). Collagen (its concentration and solubility) might affect the quality of meat (Chriki et al, 2013;Dubost et al, 2013).…”
Section: Ns Nscontrasting
confidence: 66%
See 2 more Smart Citations
“…In another study, reported by Duma‐Kocan et al ., 21 cooking and baking at 80–90 °C and 150–175 °C, respectively, decreases the water content in the dorsi muscle of wild boars as a result of the density of the tissue structure and the fat content in the meat after an increase in the heat treatment. This development contributes more to a favourable texture parameter such as hardness and and gumminess.…”
Section: Heat Treatment Intensitymentioning
confidence: 83%